Pengaruh Sertifikasi Halal, Halal Awareness, dan Religiusitas Terhadap Keputusan Pembelian Produk Mixue Ice Cream & Tea di Kabupaten Lamongan - Sulistyani, Riris Dewi; Fahrullah, (Universitas Negeri Surabaya, 2024)
Purchasing decisions for halal products are increasingly becoming a concern for consumers, especially in Indonesia with a majority Muslim population. This study aims to analyze the effect of halal certification, halal awareness and religiosity on purchasing decisions for Mixue Ice Cream & Tea products in Lamongan Regency. The research method used is quantitative with data collection techniques through questionnaire surveys distributed to 100 respondents and selected based on certain criteria using purposive sampling techniques. The results showed that the halal certification variable partially had no effect on purchasing decisions, while the halal awarenenss and religiosity variables partially had a positive and significant effect on purchasing decisions. The results of the F test show that the variables of halal certification, halal awareness, and religiosity simultaneously have a positive and significant effect on purchasing decisions. The conclusion of this study emphasizes the importance of these three factors in influencing consumer decisions to buy halal products.